Group B Streptococcus in the urine in nonpregnant adults: Disease or distraction? - Nicole Mongilardi; Brigid M. Wilson; Taissa A. Bej; Janet M. Briggs; Richard E. Banks; Sunah Song; Robin L. P. Jump; Federico Perez (Cambridge University Press, 2022)
In this large, retrospective cohort study, we used administrative data to evaluate nonpregnant adults with group B Streptococcus (GBS) bacteriuria. We found greater all-cause mortality in those with urinary tract infections compared to asymptomatic bacteriuria. Differences in patients' baseline characteristics and the 1-year mortality rate raise the possibility that provider practices contribute to differences observed.